A genetic and structural analysis of the yeast Vps15 protein kinase: evidence for a direct role of Vps15p in vacuolar protein delivery. - Herman, P K (1991)
The yeast VPS15 gene encodes a novel protein kinase homolog that is required for the sorting of soluble hydrolases to the yeast vacuole. In this study, we extend our previous mutational analysis of the VPS15 gene and show that alterations of specific Gps15p residues, that are highly conserved among all protein kinase molecules, result in the biological inactivation of Vps15p. Furthermore, we demonstrate here that short C-terminal deletions of Vps15p result in a temperature-conditional defect in vacuolar protein sorting. Immediately following the temperature shift, soluble vacuolar hydrolases, such as carboxypeptidase Y and proteinase A, accumulate as Golgi-modified precursors within a saturable intracellular compartment distinct from the vacuole. This vacuolar protein sorting block is efficiently reversed when mutant cells are shifted back to the permissive temperature; the accumulated precursors are rapidly processed to their mature forms indicating that they have been delivered to the vacuole. This rapid and efficient reversal suggests that the accumulated vacuolar protein precursors were present within a normal transport intermediate in the vacuolar protein sorting pathway. In addition, this protein delivery block shows specificity for soluble vacuolar enzymes as the membrane protein, alkaline phosphatase, is efficiently delivered to the vacuole at the non-permissive temperature. Interestingly, the C-terminal Vps15p truncations are not phosphorylated in vivo suggesting that the phosphorylation of Vps15p may be critical for its biological activity at elevated temperatures. The rapid onset and high degree of specificity of the vacuolar protein delivery block in these mutants suggests that the primary role of Vps15p is to regulate the sorting of soluble hydrolases to the yeast vacuolar compartment.